The Phosphinomethylmalate Isomerase Gene pmi, Encoding an Aconitase-Like Enzyme, Is Involved in the Synthesis of Phosphinothricin Tripeptide in Streptomyces viridochromogenes - Heinzelmann, E. (American Society for Microbiology, 2001)
Streptomyces viridochromogenes Tü494 produces the antibiotic phosphinothricin tripeptide (PTT). In the postulated biosynthetic pathway, one reaction, the isomerization of phosphinomethylmalate, resembles the aconitase reaction of the tricarboxylic acid (TCA) cycle. It was speculated that this reaction is carried out by the corresponding enzyme of the primary metabolism (C. J. Thompson and H. Seto, p. 197–222, in L. C. Vining and C. Stuttard, ed., Genetics and Biochemistry of Antibiotic Production, 1995). However, in addition to the TCA cycle aconitase gene, a gene encoding an aconitase-like protein (the phosphinomethylmalate isomerase gene, pmi) was identified in the PTT biosynthetic gene cluster by Southern hybridization experiments, using oligonucleotides which were derived from conserved amino acid sequences of aconitases. The deduced protein revealed high similarity to aconitases from plants, bacteria, and fungi and to iron regulatory proteins from eucaryotes. Pmi and the S. viridochromogenes TCA cycle aconitase, AcnA, have 52% identity. By gene insertion mutagenesis, a pmi mutant (Mapra1) was generated. The mutant failed to produce PTT, indicating the inability of AcnA to carry out the secondary-metabolism reaction. A His-tagged protein (Hispmi*) was heterologously produced in Streptomyces lividans. The purified protein showed no standard aconitase activity with citrate as a substrate, and the corresponding gene was not able to complement an acnA mutant. This indicates that Pmi and AcnA are highly specific for their respective enzymatic reactions.